Perhitungan Alokasi Dana Bagi Hasil Pajak Rokok Pada Badan Pengelola Pendapatan Daerah Provinsi Jawa Tengah Triwulan Iv Tahun 2016 - Akhsanur Rifai; Resi Yudhaningsih (Politeknik Negeri Semarang, 2018)
The reseach aims to know determine the procedure for calculating the allocation of funds from cigarette tax revenues quarter IV to Regency / City of Central Java Province On Central Java Regional Income Management Board. Writing method used are the method of description and exposition. The calculation of the allocation of revenue sharing funds for tobacco tax quarter IV which is in use is the realization of 2016. The results of the calculating the allocation of funds from cigarette tax revenues quarter IV to Regency / City between of Central Java Province On Central Java Regional Income Management with regulation governer 67 in 2014 Show result different. Different because that the share of cigarette tax data the number of population used is the data of population in 2014, when it should be calculated with the data of the population in 2015.